Marketing Strategy Analysis Using STP Strategy (Segmentation, Targeting, Positioning) at PT. Berkah Ridho Cinta Indonesia - Hellenna Kusuma Ningrum; Maulidyah Indira Hasmarini (Income Journal Of Economics Development, 2024)
This research aims to explain the STP marketing strategy (Segmenting, Targeting, Positioning) in marketing Brownies Cinta business products at PT. Berkah Ridho Cinta Indonesia. The method used in this research is descriptive qualitative, the data used in this study are primary data and secondary data using descriptive qualitative. In the STP marketing analysis, geographic segmentation is focused on the Surakarta Residency area, which has a higher potential for repeat purchases. In demographic segmentation, the target audience encompasses consumers ranging from children to the elderly and spans various economic levels. Psychographic segmentation is concentrated on consumers who exhibit a preference for specific foods or snacks, particularly cakes or brownies. The implementation of STP marketing strategy is anticipated to support the business performance and the product performance of Brownies Cinta enterprise, enabling consumers to become more acquainted with the products produced and contributing to the expansion of market share. The researcher concludes that the application of the STP strategy in the Brownies Cinta enterprise significantly influences the increase in sales, as elucidated by the results of interviews and observations conducted by the researcher.